Impact of lympho‐vascular space invasion on tumor characteristics and survival outcome of women with low‐grade serous ovarian carcinoma. Issue 2 (8th August 2017) - Matsuo, Koji; Wong, Kwong‐Kwok; Fotopoulou, Christina; Blake, Erin A.; Robertson, Sharon E.; Pejovic, Tanja; Frimer, Marina; Pardeshi, Vishakha; Hu, Wei; Choi, Jong‐Sun; Sun, Charlotte C.; Richmond, Abby M.; et al.
Abstract : Background and Objectives: To examine association of lympho‐vascular space invasion (LVSI) with clinico‐pathological factors and to evaluate survival of women with low‐grade serous ovarian carcinoma containing areas of LVSI. Methods: This is a multicenter retrospective study examining consecutive cases of surgically treated stage I‐IV low‐grade serous ovarian carcinoma ( n = 178). Archived histopathology slides for the ovarian tumors were reviewed, and LVSI was scored as present or absent. LVSI status was correlated to clinico‐pathological findings and survival outcome. Results: LVSI was seen in 79 cases (44.4%, 95% confidence interval [CI] 37.1‐51.7). LVSI was associated with increased risk of omental metastasis (87.0% vs 64.9%, odds ratio [OR] 3.62, P = 0.001), high pelvic lymph node ratio (median 12.9% vs 0%, P = 0.012), and malignant ascites (49.3% vs 32.6%, OR 2.01, P = 0.035). On multivariable analysis, controlling for age, stage, and cytoreductive status, presence of LVSI in the ovarian tumor remained an independent predictor for decreased progression‐free survival (5‐year rates 21.0% vs 35.7%, adjusted‐hazard ratio 1.57, 95%CI 1.06‐2.34, P = 0.026). LVSI was significantly associated with increased risk of recurrence in lymph nodes (OR 2.62, 95%CI 1.08‐6.35, P = 0.047). Conclusion: LVSI in the ovarian tumor is associated with adverse clinico‐pathological characteristics and decreased progression‐free survival in women with low‐grade serous ovarian carcinoma.